PENDAMPINGAN PENGOLAHAN DAN PENGEMASAN DENDENG DAGING KERBAU FERMENTASI DI KELOMPOK PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA DESA BATU BULAN KECAMATAN MOYO HULU - Ihlana Nairfana; Chairul Anam Afgani; Ratna Nurmalita Sari; Veni Rori Setiawati (Universitas Mataram, 2022)
Local residents of Batu Bulan Village have been processing buffalo meat into traditional flavored jerky called “raret”. The jerky is marinated in salt and tamarin juice therefore has a less varied taste. Besides that, the long drying time of the jerky makes the texture become tough. Therefore ready-to-eat jerky is one of the innovations to make beef jerky easier to process and maintain its nutritional content. Fermentation lactic acid bacteria (BAL) is one well-known processing technique that are considered most suitable. The aim of this program is to increase the added value of buffalo jerky through processing and packaging innovation. The method used is socialization, counseling, as well as training and mentoring. Furthermore, the implementation of the socialization event took place at the Batu Bulan Village Office which was attended by the woman empowerment and village officials. The results obtained from this activity are the increased ability of Batu Bulan woman empowerment in processing and packaging ready-to-eat buffalo jerky. There has been an increase in the ability of Batu Bulan women in developing their business from the aspect of producing and product packaging.